Little Shrew - Miyakoshi, Akiko, 1982- (Kids Can Press, 2024)
"This collection of three interconnected stories follows the life of Little Shrew as he goes about his everyday activities of commuting to work to reflecting on his hopes and dreams to welcoming his friends for a visit."--